ASPEK EPISTEMOLOGI FILSAFAT HUKUM INDONESIA - Max Boli Sabon (Masalah-Masalah Hukum, 2012)
Abstract Many people say that the implementation of law in Indonesia has been on the track, nonetheless, it is only the way of putting into effect that is not wise enough. From  the point of view of the aspect of onthology of philosophy, the application of law in Indonesia is having no problem so far. On the other hand, the problem is in its epistemology. The duty of philosophy of law is to give explanation of such phenomenon. The problem is therefore laid down in epistemology, it is wise to use the school that talks a lot about epistemology of law. Furthermore, Indonesia is a pluralistic society, for that reason, the choice to use the Modern Natural Law as its approach is considered to be as one of the alternative, for the school itself is emphasizing upon the epistemology of law as well as the custom law which as the characteristic of pluralism of Indonesia. The study of epistemology of philosophy of law  in Indonesia, with the approach through the Modern Natural Law toward custom law of Indonesia is supported by the legal studies progressively that may explain the phenomenon of the confused and depraved enforcement of law in Indonesia. Keywords: epistemology of law, philosophy of law, modern natural law, custom law, legal studies progressively Abstrak Banyak orang mengatakan pengaturan hukum di Indonesia sudah baik; hanya cara pelaksanaannya yang tidak baik. Gejala ini berarti dari aspek ontologi filsafat hukum, hukum di Indonesia tidak bermasalah. Yang bermasalah adalah aspek epistemologinya. Filsafat hukum bertugas menjelaskan gejala ini. Oleh karena permasalahnnya terletak di bidang epistemologi, maka digunakan mazhab hukum yang banyak membicarakan tentang epistemologi hukum. Selain itu, Indonesia adalah bangsa yang majemuk. Untuk itu pilihannya antara lain adalah Mazhab Hukum Alam Modern karena banyak berbicara tentang epistemologi hukum sekaligus hukum adat sebagai ciri kemajemukan Indonesia. Studi epistemologi filsafat hukum Indonesia dengan pendekatan Mazhab Hukum Alam Modern terhadap hukum adat Indonesia yang didukung oleh pemikiran hukum secara progersif, dapat menjelaskan gejala carut-marutnya cara pelaksanaan hukum di Indonesia .   Kata Kunci: epistemologi hukum, filsafat hukum, hukum alam modern, hukum adat, pemikiran hukum progresif